Single excavation face method for super-large-span bifurcated tunnels. Issue 4 (28th August 2021) - Tan, Zhongsheng; Zhou, Zhenliang; Kong, Heng; Zhao, Bojian; Zhao, Jinpeng
Abstract : Bifurcated tunnels have two major engineering problems of large span and small interval simultaneously, and they pose higher demands on design and construction technology. The Liantang tunnel has a maximum span of 30.1 m, a minimum interval of only 1.05 m and a single excavation face; the existing construction method cannot meet the demand. Based on these features, this paper proposes a reverse expanding excavation method and a stepwise controlled blasting excavation method. By numerical calculation and field testing, the stability and mechanical characteristics of the surrounding rock and primary support using the two methods were researched. The results show that the reverse expanding excavation method, by excavating the pilot tunnel first and then reversely excavating the remaining part, achieves stepwise excavation of the super-large-span tunnel, provides mechanised working conditions and avoids multiple conversions of the excavation method. The stepwise controlled blasting excavation method, by grouting and reinforcing the shared rock first, and then controlled blasting of the later tunnel in steps, ensures the stability of the shared rock, reduces the construction influence of the later tunnel on the existing tunnel and omits the construction of a mid-partition. This study can provide a reference for future similar projects.